IMPLEMENTASI KEBIJAKAN PELAYANAN PUBLIK BIDANG PERIZINAN DI DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU (DPMPTSP) KELURAHAN WARAKAS TANJUNG PRIOK JAKARTA UTARA - Mustika, Windy; Tuswoyo, Tuswoyo; Dahuri, Adin (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study is based on the relaxation of licensing policies that have not been running effectively in the One-Stop Integrated Services Investment Office (DPMPTSP) of Warakas Village, Tanjung Priok District, North Jakarta. Services that have not been effective due to the handling of employees to the community has not been running smoothly and the existing infrastructure is not adequate. The purpose of this study was to determine and analyze how effective the implementation of public service policies in the Investment Office with a One-Stop Integrated Service model (DPMPTSP) Warakas Village, Tanjung Priok District, North Jakarta. To further analyze what are the obstacles that occur in the implementation of these policies and what efforts or solutions are made to overcome these obstacles. The theory used to dissect this problem is translated into four dimensions, namely communication, resources, disposition and this research is descriptive with a qualitative approach. The results showed that the relaxation policy in general has been running quite well. Nevertheless there are still some things that need to be fixed. Officers should be increased in capacity.provide services to the community concerned. In addition, some interested communities have not fully understood the permit management procedure. Some things are done as an effort to overcome these obstacles or obstacles. Employees should have developed their abilities by providing regular training. Socialization of licensing management procedures to the community needs to be intensified. The more intensive the socialization is done, the more people understand the procedure in question